2015
DOI: 10.1111/ppa.12443
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium oxide nanoparticles induce systemic resistance in tomato against bacterial wilt disease

Abstract: Bacterial wilt is a serious problem affecting many important food crops. Recent studies have indicated that treatment with biotic or abiotic stress factors may increase the resistance of plants to bacterial infection. This study investigated the effects of magnesium oxide nanoparticles (MgO NP) on disease resistance in tomato plants against Ralstonia solanacearum, as well as its antibacterial activity. The roots of tomato seedlings were inoculated with R. solanacearum and then immediately treated with MgO NP; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
92
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 223 publications
(100 citation statements)
references
References 39 publications
3
92
0
Order By: Relevance
“…Rapid production of reactive oxygen species (ROS) has been observed in tomato roots treated with MgO (Imada et al, 2016). Thus, ROS production was analysed in A. thaliana plants treated with MgO using diaminobenzidine (DAB), which detects hydrogen peroxide (H 2 O 2 ), one of several ROS.…”
Section: Involvement Of Nadph Oxidase In Mgo-induced Defence Againstmentioning
confidence: 99%
See 3 more Smart Citations
“…Rapid production of reactive oxygen species (ROS) has been observed in tomato roots treated with MgO (Imada et al, 2016). Thus, ROS production was analysed in A. thaliana plants treated with MgO using diaminobenzidine (DAB), which detects hydrogen peroxide (H 2 O 2 ), one of several ROS.…”
Section: Involvement Of Nadph Oxidase In Mgo-induced Defence Againstmentioning
confidence: 99%
“…In A. thaliana , ROS production is dependent on AtRBOHD, a member of the 10 RBOHs (RBOHA to J) that are homologous to NbRBOHB, which is triggered by both biotic and abiotic stresses leading to plant immunity (Liu & He, ). In a previous study (Imada et al ., ), rapid generation of ROS was observed in tomato roots treated with MgO, suggesting that ROS would be involved in MgO‐i DARS. The present study reveals how plant hormone and ROS signalling pathways influence MgO‐i DARS in A. thaliana .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…[13] reported that the controlling effect increases in the administered dosage of nanoparticle and there exists a direct correlation between the administered dosage and controlling effect, the concentration of 2% MgoNps had the greatest effect in both liquid and solid media, [14] reported that the when roots were drenched with MgoNps suspension prior to inoculation with pathogen, the incidence of disease was significantly reduced. Also, these results agree with selko Dutch company research regarding close conformity with finding of [5].…”
Section: In Vitro Antifungal Assaysmentioning
confidence: 99%